2008
DOI: 10.1016/j.jvs.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of infrapopliteal angioplasty for chronic critical limb ischemia

Abstract: The technical success and subsequent durability of crural angioplasty are limited compared with bypass surgery, but the clinical benefit is acceptable because limb salvage rates are equivalent to bypass surgery. Further studies are necessary to determine the proper role of infrapopliteal angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
321
3
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(370 citation statements)
references
References 34 publications
(10 reference statements)
14
321
3
21
Order By: Relevance
“…In line with the BASIL‐trial, indirect comparisons of endovascular procedures66, 67 and open bypass surgery using a vein graft11 show similar results with respect to 1‐year limb salvage and mortality rates in CLI, both ranging from 85% to 90%, but a higher need for reinterventions after endovascular therapy 68. This increased reintervention rate corresponds with an increase in the number of endovascular interventions in both claudication and CLI over the years that outnumbers the decline in open surgical interventions.…”
Section: Revascularization Strategies In CLImentioning
confidence: 72%
“…In line with the BASIL‐trial, indirect comparisons of endovascular procedures66, 67 and open bypass surgery using a vein graft11 show similar results with respect to 1‐year limb salvage and mortality rates in CLI, both ranging from 85% to 90%, but a higher need for reinterventions after endovascular therapy 68. This increased reintervention rate corresponds with an increase in the number of endovascular interventions in both claudication and CLI over the years that outnumbers the decline in open surgical interventions.…”
Section: Revascularization Strategies In CLImentioning
confidence: 72%
“…In a meta-analysis comparing the results of the surgical and endovascular approach of BTK area, Romiti et al [32] reported a rate of limb salvage at 3 years that was comparable for the two techniques (PTA 82.4 ± 3.4, surgery 82.3 ± 3.0). Several other studies [23][24][25][26][27][28][29][30] evaluated the effectiveness of PTA in diabetic foot patients, but these studies are limited by their main conditions, including a heterogeneous population with BTK and/or ATK disease.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transluminal angioplasty (PTA) or balloon angioplasty is the current standard of therapy, with a technically successful result (<30% residual stenosis) in the majority of cases (77-100%), but is limited by high restenosis rates [16,17]. Flexible, low profile, balloons have enhanced the ability to cross, and successfully treat, focal, multi-focal, diffuse, and occlusive lesions.…”
Section: Percutaneous Transluminal Angioplastymentioning
confidence: 99%